Experimental analysis and simulation of a centrifugal jet fan for impulse ventilation systems. (1st October 2022) - Xue, Yu; Li, Xiaomeng; Li, Ning; Zheng, Shu; Wang, Zhichao
Abstract: Centrifugal jet fans are usually used to stir evenly, remove local airflow blind spots, and improve air quality. They are widely used in HAVC systems of garage buildings recently. However, there are few in-depth studies on its modeling methods, and even the experimental verification of the most basic centrifugal jet fan simulation model has not been fully demonstrated. This paper combines experimental verification with numerical simulation to investigate the appropriate modeling method and jet characteristics of centrifugal jet fans for impulse ventilation systems. Experimental data showed that the air volume of each nozzle of the centrifugal jet fan was different, and that even outlet velocity of a single nozzle was not uniform. Velocity decreased slightly in the jet core area and then decreased gradually until it approached the ambient velocity, while the amount of air entrained by the jet was approximately linear with respect to the jet range. In addition, the design key points and methods of impulse ventilation systems was summarized. CFD was used to simulate the flow field of centrifugal jet fans. Two modeling strategies, involving accurate boundary conditions based on experimental data, and simplified velocity boundary conditions, were used, and displayed differing characteristics. When designers focus on the coverage range of jet fans and the velocity distribution at the far-field, or the operation performance of jet fans in HAVC systems, the simplified velocity boundary conditions can be used. When the aim is to study and optimize nozzle, an accurate model and boundary conditions should be utilized. Highlights: Measurement data were provided for a centrifugal jet fan as applied in impulse ventilation systems. Proper modeling methods of centrifugal jet fans in different application scenarios were discussed. The design key points of impulse ventilation systems for garage buildings were summarized.